Pressure leaching of chalcopyrite with oxalic acid and hydrogen peroxide - Turan, M. Deniz; Sari, Zeynel Abidin; Nizamoglu, Hasan (Elsevier, 2021)
This study investigated the dissolution behavior of metals from chalcopyrite concentrate in a pressure reactor system in the presence of hydrogen peroxide by oxalic acid leaching. The fact that the compounds formed by copper and iron with oxalic acid had different dissolution coefficients showed that metals could be selectively extracted based on the leaching temperature. The effects of various leaching parameters on metal extraction in the autoclave system were investigated at different H2O2 concentrations (1-5 M), H2C2O4 concentrations (25-125 g/L), leaching temperatures (318-443 K) and leaching times (15-180 min). While iron and copper extraction as a result of 180 min of leaching with 5 M H2O2, 318 K and 100 g/L H2C2O4 was respectively 90.6% and 1.73%, 88.5% of copper and 2.11% of iron could be extracted as a result of 180 min of leaching with 3 M H2O2, 443 K and 100 g/L H2C2O4. The reversal of the copper and iron extraction dissolution behavior started after the leaching temperature of 378 K. In the XRD analysis of leach residues obtained at low leaching temperatures, CuC2O4 peaks were dominant, while at high temperature conditions, Fe2O3 peaks were dominant. (c) 2020 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Chalcopyrite; Pressure leaching; Copper; Oxalic acid; Hydrogen peroxide; Autoclave